Cat's meow - Farber, Erica; Sansevere, John R.; Mayer, Mercer 1943- (New York Racine, Wis. Golden Book Western Pub., 1994)
LC finds a cat who follows him to school--much to the principal's distress--and then presents him and his friends with a litter of kittens
"A Mercer Mayer Ltd./J.R. Sansevere book."
7 - 9 years
68131
Keywords: Cats -- Fiction